Nine Contradictory Observations About Girls’ and Boys’ Upbringing and Education – The Strength-Based Approach as the Way to Eliminate the Gender Gap - Määttä, Kaarina; Uusiautti, Satu (Frontiers in Education, 2020)
Several studies in the 1970s and 1980s have showed how girls’ courage or willingness to bring out their talents and strengths at school is hindered by many factors. The self-esteem of girls who are known to be talented decreases especially during their adolescence. This phenomenon is connected to girls’ ability to notice conflicting expectations in their environment. They realize that they are expected to possess certain traditional female characteristics such as passiveness, adjustment, sensitivity to others’ expectations, and altruism. They are not expected to show competitiveness. At the same time, girls are expected to perform well at school. Girls learn to regulate their behaviors and study quietly, but this could also hinder their talents to come forward. Still, they pursue perfect scores that eventually do not bring them satisfaction. Earlier research has showed that teachers treat girls and boys differently, based on stereo-typical assumptions about troublesome boys and compliant girls, and they also interpret reasons for girls’ and boys’ behaviors differently. The 21st century seems to both repeat and question many of the research results about gender differences. In this article, we analyze gender cap through nine viewpoints by presenting contradictory research results about girls’ and boys’ upbringing and education. It is crucial that each individual can develop their own strengths for the best of themselves and the society – regardless of their gender. As the conclusion we present the role of strength-based teaching as means to promote gender equality at school. It is based on the ideology of positive psychological research and on the fundamental idea that strengths belong to everyone. The ability to recognize and use one’s strengths has not only personal benefits in terms of increased life satisfaction but also societal benefits as strengths help facing adversities, overcome difficulties, and prevent malaise, and increase wellbeing in general. When people flourish, not only the people but also the society succeeds—and it all starts from school. The strength-based approach can direct teachers’ attention away from good-girl-expectations to universal and genderless strengths, and help girls find success in life that is based on well-being and profound understanding of one’s potential.